GROUND RADAR STEALTH BERBASIS MICROWAVE ABSORBER DALAM PERANG UDARA - Harry Cahyadi Wijaya Kusuma; Supri Abu; Bambang Kustiawan (Universitas Perrtahanan Indonesia (UNHAN), 2023)
This research background is based on scenario changes of war concepts from conventional to technology-based, where stealth is one of the technologies which is important in air warfare. This fact creates phenomena that show “There’s no stealth technology had been applied to protect Ground Radar Station as an enemy centre of gravity”, related to that research question which is formulated on how to design an adaptive “Ground Radar Stealth” (GRS) and why it is needed. All relevant theories used in this research are stealth, Radar, and Microwave Absorbers. Research Methode that being used is descriptive qualitative by comparing theories and using QFD as tools. In designing GRS some informants are involved such as military expert, academic, commander of fighter aircraft squadron and Radar. The result of this research is formulating a GRS design that had been adjusted with the theories to apply to GRS and is also useful. To make this research can be realised support in the form of funds, time, and cooperation from the Indonesian Air Force Itself and Academic sources are needed. Also, to optimize GRS design, it is suggested to create layers of defence like an Iron dome, but adjusted to the Indonesian Geographical environment